New Oscillatory Behavior of Third-Order Nonlinear Delay Dynamic Equations on Time Scales - Li Gao; Quanxin Zhang; Shouhua Liu (Abstract and Applied Analysis)
A class of third-order nonlinear delay dynamic equations on time scales is studied. By using the generalized Riccati transformation and the inequality technique, four new sufficient conditions which ensure that every solution is oscillatory or converges to zero are established. The results obtained essentially improve earlier ones. Some examples are considered to illustrate the main results.